Locomotor performance of cane toads differs between native-range and invasive populations. Issue 7 (12th July 2017) - Kosmala, Georgia; Christian, Keith; Brown, Gregory; Shine, Richard
Abstract : Invasive species provide a robust opportunity to evaluate how animals deal with novel environmental challenges. Shifts in locomotor performance—and thus the ability to disperse—(and especially, the degree to which it is constrained by thermal and hydric extremes) are of special importance, because they might affect the rate that an invader can spread. We studied cane toads ( Rhinella marina ) across a broad geographical range: two populations within the species' native range in Brazil, two invasive populations on the island of Hawai'i and eight invasive populations encompassing the eastern, western and southern limits of the toad invasion in Australia. A toad's locomotor performance on a circular raceway was strongly affected by both its temperature and its hydration state, but the nature and magnitude of those constraints differed across populations. In their native range, cane toads exhibited relatively low performance (even under optimal test conditions) and a rapid decrease in performance at lower temperatures and hydration levels. At the other extreme, performance was high in toads from southern Australia, and virtually unaffected by desiccation. Hawai'ian toads broadly resembled their Brazilian conspecifics, plausibly reflecting similar climatic conditions. The invasion of Australia has been accompanied by a dramatic enhancement in the toads' locomotor abilities, and (in some populations) by an ability to maintain locomotor performance even when the animal is cold and/or dehydrated. The geographical divergences in performance among cane toad populations graphically attest to the adaptability of invasive species in the face of novel abiotic challenges.